2017
DOI: 10.1002/dneu.22561
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal development of electrophysiological and histological properties of sensory sural nerves in male rats that were maternally deprived and artificially reared: Role of tactile stimulation

Abstract: Early adverse experiences disrupt brain development and behavior, but little is known about how such experiences impact on the development of the peripheral nervous system. Recently, we found alterations in the electrophysiological and histological characteristics of the sensory sural (SU) nerve in maternally deprived, artificially reared (AR) adult male rats, as compared with maternally reared (MR) control rats. In the present study, our aim was to characterize the ontogeny of these alterations. Thus, male pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 78 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Since the SUn is mainly composed of myelinated sensory axons, disturbances in the axonal propagation of action potentials due to a lack of myelin could be expected to result in peripheral neuropathies (Melo et al, 2021). Consequently, it could be expected that a relatively large proportion of axons in nerves with peripheral neuropathy would present Thus, the alteration of sensory nerve functionality found in offspring that did not receive adequate sensory and social stimulation during critical periods of development, either due to being deprived of the mother and littermates (Segura et al, 2014;Zempoalteca et al, 2018) or because they were raised in litters of extreme size (this study), resulting in poorer early nutrition, could explain certain neuropathies or even disturbances in social interactions due to the fact that social signals do not reach adequately the CNS and therefore the interpretation and response to these signals may be correspondingly inadequate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the SUn is mainly composed of myelinated sensory axons, disturbances in the axonal propagation of action potentials due to a lack of myelin could be expected to result in peripheral neuropathies (Melo et al, 2021). Consequently, it could be expected that a relatively large proportion of axons in nerves with peripheral neuropathy would present Thus, the alteration of sensory nerve functionality found in offspring that did not receive adequate sensory and social stimulation during critical periods of development, either due to being deprived of the mother and littermates (Segura et al, 2014;Zempoalteca et al, 2018) or because they were raised in litters of extreme size (this study), resulting in poorer early nutrition, could explain certain neuropathies or even disturbances in social interactions due to the fact that social signals do not reach adequately the CNS and therefore the interpretation and response to these signals may be correspondingly inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Segura et al (2014) found that artificially reared rat pups deprived of sensory feedback from their mother and littermates showed as adults a significant decrement in the area of the compound action potential (CAP), which has been considered a representative index of the number of axons activated in nerves (Stys et al, 1991), and a significant reduction in myelin thickness of axons in the SUn. In the rat, such effects have a critical time window between PND7 and PND14 (Zempoalteca et al, 2018). But notably, the above effects were largely prevented if artificially reared pups were raised with one littermate inside the cup of isolation.…”
Section: Introductionmentioning
confidence: 99%
“…There are no publications studying electrophisiological modifications in somatic primary afferents in mice submitted to MS and only a few have evaluated the effects of ELS in the electrophysiological function of nociceptive neurons in rats (Segura et al, 2014; Zempoalteca et al, 2018). These two previous studies differ from ours in some aspects as the strain, the ELS model and that they evaluated the electrophysiological characteristics of the entire nerve, whilst we have carried out recordings from single myelinated Aδ‐fibres.…”
Section: Discussionmentioning
confidence: 99%
“…During the breeding process the MR pups and their foster dams were housed in clear Plexiglas cages (30 × 15 × 14 cm), with Purina Rat Chow and water available ad libitum, and left undisturbed except during bedding and cage change. For the AR group, the pups were selected randomly for artificial reared subject to a surgery, which consists in the implantation of a cannula through the cheek where milk is supplied [28, 30]. The surgery was performed according to previous works [27, 31].…”
Section: Methodsmentioning
confidence: 99%
“…The pups were stimulated with the paintbrush along the back with anterior-posterior movements for 45 sec, five times per day, daily until pnd21 of age [34]. Although this additional stimulation doesn´t mimics the maternal stimulation, it was showed that this is enough to prevent some effects of total maternal deprivation during early life, as alterations in the myelination and electrophysiological function of the sural nerve [30]. In order to avoid possible developmental alterations associated with the absence of maternal odours [35, 36], wood chips from mother-litters cage were used as an odoriferous stimulus.…”
Section: Methodsmentioning
confidence: 99%